Patienten- und bedarfsgerechte Prozessgestaltung in der zentralen Notaufnahme: Ein interdisziplinäres Best-Practice-Vorgehen zur Optimierung von Abläufen in der Notaufnahme unter Einbezug der relevanten Stakeholderinteressen. - Ristau, Patrick; Pfeuffer, Stephanie; Büttner, Jens (Pflegewissenschaft, 2020)
The emergency department of a hospital is often the first point of contact for sick and injured patients. In order to bundle resources and capacities and to provide patients with optimal care according to their individual treatment urgency, hospitals establish central emergency departments. Little has been known about the individual needs of patients in the emergency room and the resulting consequences for clinical and organizational processes. For this reason, this best practice project focuses on patient needs and derives problem- and demand-oriented interventions from them. These are developed, tested and subsequently implemented or improved with recourse to relevant stakeholder interests.